Memory Enhancing Effect of Ethanolic Extract of Stevia rebaudiana (Bert.) - Divya S Juyal; Ganga Bisht; Arun Kumar (International Journal of Phytomedicine, 2010)
Suspension of ethanolic extract of leaves of Stevia rebaudiana bert. in gum acacia were administered orally to evaluate the memory enhancing activity in the aged rats. Memory enhancing effect was evaluated by using Morris water maze and elevated plus maze. Mean escape latency time (ELT) calculated each day during acquisition trial was used as an index of acquisition and mean time spent in target quadrant in search of missing platform provided an index of retrieval. Significant reduction in transfer latency (TL) value of retention indicated improvement of memory. Significant memory enhancing effect of ethanolic extract Stevia rebaudiana was observed in aged rats at 200 mg/kg p.o. dose.